2022
DOI: 10.1073/pnas.2202926119
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric inhibitors targeting the calmodulin-PIP2 interface of SK4 K + channels for atrial fibrillation treatment

Abstract: The Ca 2+ -activated SK4 K + channel is gated by Ca 2+ –calmodulin (CaM) and is expressed in immune cells, brain, and heart. A cryoelectron microscopy (cryo-EM) structure of the human SK4 K + channel recently revealed four CaM molecules per channel tetramer, where the apo CaM C-lobe and the holo CaM N -lobe interact with the proximal carboxyl terminus and the linker S4–S5, respectively, to ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 38 publications
(84 reference statements)
1
18
0
Order By: Relevance
“…Inhibition of K Ca 3.1, especially in combination with targeting K Ca 2.2, can be interesting for influencing atrial fibrillation (AF). It was shown recently that inhibition if K Ca 3.1 or K Ca 2.2 in isolation may reduce AF [ 56 , 57 , 58 ]. It may be an interesting scenario to target both ion channels simultaneously, and based on our results Cm39 would be a suitable candidate for a dual-action drug candidate.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of K Ca 3.1, especially in combination with targeting K Ca 2.2, can be interesting for influencing atrial fibrillation (AF). It was shown recently that inhibition if K Ca 3.1 or K Ca 2.2 in isolation may reduce AF [ 56 , 57 , 58 ]. It may be an interesting scenario to target both ion channels simultaneously, and based on our results Cm39 would be a suitable candidate for a dual-action drug candidate.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that blocking KCa3.1 overexpression in canine atrial tissue macrophages using TRAM-34 reduced susceptibility to AF [ 9 ]. Recent studies have shown that the KCa3.1 channel allogenic blocker BA6b9 significantly prolonged the atrial and effective atrioventricular refractory periods in the isolated hearts of rats and reduced AF induction ex vivo [ 17 ]. This evidence supports the proarrhythmic role of KCa3.1.…”
Section: Discussionmentioning
confidence: 99%
“…These SK4 K + channels are well known to be expressed by immune cells such as T cells, B cells, and macrophages, as well as by endothelial cells, fibroblasts, and proliferating smooth muscle cells of the vascular system ( 30–33 ). Recently, we demonstrated that the SK4 channel protein is widely expressed in the atria of rat and human hearts and to a lesser extent in the ventricles ( 23 ). A novel allosteric blocker, BA6b9, was designed to interact with the calmodulin-PIP2 binding domain, a previously untargeted region of these SK4 channels, at the specific interface of the proximal C-terminus and the linker S4–S5 domain ( 23 ).…”
Section: Introductionmentioning
confidence: 99%